Pembacaan Martabat Manusia Sebagai Teks Untuk Konstruksi Budaya Damai ala Levinas dan Murdoch - Fiktor Jekson Banoet (Institut Agama Kristen Negeri Tarutung, 2020)
AbstractIn this century, we repeat religion-based violence and mixed with politics from the past. Beyond that, the basis of this form of violence is because it emphasizes the aspects of exclusion in diversity. All of these forms have an impact on the lowest universal value, namely human dignity (also the nature). We would indeed talk about the dignity of creation including the universe. But at this time, the purpose of this paper will only discuss how dignity has reflected only on the limits of human dignity from a theological-philosophical perspective. Especially for building a culture of peace. The dignity of the 'Liyan' must be seen as 'text'. There are many approaches and disciplines for that. However, I try to construct it at the most basic level of efforts to build a culture of peace, namely the interpersonal level. Therefore, the ethics of relations is using to re-read human dignity in diversity to reach the point of encounter, and the values of dignified relation rather than exclusion, and all violence forms as a final consequence.Keywords: the culture of peace, violence, theological-philosophical, ethical relations, diversity.